2013
DOI: 10.1177/1077546313486275
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of elastic and modal parameters in composites using vibration analysis

Abstract: This study presents the application of vibration analysis in the determination of elastic constants (i.e. Young’s modulus in fiber direction, transverse Young’s modulus, and shear modulus) and modal damping ratios of a unidirectional composite beam. The frequency domain approach is used for the estimation of material constants, whereas modal damping ratios are predicted by the use of short-time Fourier transform (STFT). An analytical expression of the STFT for the free vibration response of a viscously damped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Combined finite element and frequency response was carried out by references [ 22 , 23 ], who aimed to study the dynamic properties of the composite material. The study of the damping properties and modelling of the dynamic properties have been conducted by many investigators [ 24 , 25 , 26 , 27 , 28 ] using the finite element methods to predict the natural frequency and mode shapes. These results allow us to characterize the dynamic behaviors for metals and new composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Combined finite element and frequency response was carried out by references [ 22 , 23 ], who aimed to study the dynamic properties of the composite material. The study of the damping properties and modelling of the dynamic properties have been conducted by many investigators [ 24 , 25 , 26 , 27 , 28 ] using the finite element methods to predict the natural frequency and mode shapes. These results allow us to characterize the dynamic behaviors for metals and new composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting resonant frequencies is quite common in many branches of engineering, and can be effectively used to estimate Young’s modulus. 1115 In the previous section, it was reported that each specimen was subject to a bending test (under a point tip load), based on the theory from the Experimental elastic modulus extraction approaches section. Each specimen was subject to a free vibration test (without re-clamping): a typical free decay time series is shown in Figure 6(a), in which the tip of the cantilever was displaced and released to promote a response in the first flexural mode.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, conventional signal processing techniques such as Fast Fourier Transform (FFT) [1][2][3], and Short-Time Fourier Transform (STFT) [4,5] are employed to analyze the linear and stationary signals. However, the responses of structures in the real world are inherently nonlinear according to structural health monitoring systems [6,7] and non-stationary.…”
Section: Introductionmentioning
confidence: 99%